Associations of physical activity participation trajectories with subsequent motor function declines and incident frailty: A population-based cohort study - Wang, Yang; Li, Chenglong; Ma, Yanjun; Zheng, Fanfan; Xie, Wuxiang (Frontiers in Psychiatry, 2022)
Abstract Background: Maintaining physical function and delaying frailty are of significant importance in both quality of life and health longevity for successful ageing. The objective of this study is to investigate whether different trajectories of long-term physical activity (PA) participation are associated with subsequent motor function declines and incident frailty in middle-aged and elderly adults. Methods: We used data from 8227 aged ≥50 years adults enrolled in the English Longitudinal Study of Ageing. Long-term PA participation trajectories were assessed using group-based trajectory modeling over the first 6-year period from wave 1 (2002-2003) to wave 4 (2008-2009). The longitudinal associations of PA trajectories with motor function declines and incident frailty were evaluated by a linear mixed model and Cox regression model, respectively, with follow-up of 10 years from wave 4 to wave 9 (2018-2019). Results: Five distinct trajectories of long-term PA participation were identified in the ageing cohort, including persistently low-active trajectory (N=2039), increasing active trajectory (N=1711), declining active trajectory (N=216), persistently moderate-active trajectory (N=2254), and persistently high-active trajectory (N=2007). Compared with the persistently low-active group, the participants in persistently moderate- and high-active groups experienced significantly decelerated grip strength decline, decreased gait speed decline, and faster chair rises after multiple-adjustment. Similarly, participants maintaining moderate- and high-active PA were also associated with a lower risk of incident frailty (multiple-adjusted hazard ratio: 0.70, 95% confidence interval: 0.62 to 0.80, and 0.42, 95% CI: 0.36 to 0.49, respectively), compared with those with persistently low PA. Notably, the participants with the increasing active trajectory got similar health benefits as those with persistently moderate and high levels of PA. Conclusion: In addition to persistent PA, increasing PA was linked to a slower decline in motor function and lower risk of incident frailty in the cohort. Our findings suggest that regular PA is never too late.